(untitled) (Research, Society and Development, 2021)
Inventories of Amazon invertebrates are relatively incipient and fragmented. The state of Amapá is one of the Amazonian states with a large knowledge gap regarding invertebrate biodiversity. Also, there is no record in the literature of systematic studies that focus mainly on the Acridofauna. Therefore the goal of this study was to understand the diversity and abundance of grasshoppers (Gomphocerinae) of the Environmental Protection Area of the Curiaú river, Macapá - AP. Twelve samples were collected from October 2011 to September 2012 using the active search technique with sweep nets. A total of 508 Gomphocerinae individuals were sampled and classified into five genera and twelve species. The floristic composition of sites A1 and A3, and sites A5 and A6, are considered more similar since the locusts are closely related to the vegetation. This is the first study assessing the diversity of orthopteroides in the state of Amapá. However, this pioneering study is expected to be the basis of future studies.